Growth Performance and Nutrient Utilisation as Affected by Black Pepper or Jaggery Supplementation and Feed Restriction in Broiler Chicken - Sidhu, Navjot Singh; Singh, Udeybir; Sethi, A.P.S. (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to evaluate the effects of black pepper, jaggery supplementation and feed restriction on phase wise growth performance and nutrient digestibility in broilers. In this study, 480 chicks were distributed randomly into 8 treatments having total 60 birds per treatment (4 replicates Ã— 15 chicks in each replicate. The birds in treatment T1 (control groups) were fed as per ICAR (2013) i.e. starter diet with 22% CP and 3000 Kcal/kg ME, grower diet with 21.5% CP and 3050 Kcal/kg ME and finisher diet with 19.5% CP and 3100 Kcal/kg ME.). The other treatments comprised: T2 = T1 with feed restriction (8-10 h), T3 = T1 with 0.5% blackpepper supplementation, T4 = T1 with 0.5% black pepper supplementation and feed restriction (8-10 h), T5= T1 with 1% jaggery supplementation, T6 = T1 with 1% jaggery supplementation and feed restriction (8-10 h), T7 = T1with 0.5% black pepper and 1% jaggery supplementation, T8 = T1 with 0.5% black pepper and 1% jaggery supplementation and feed restriction (8-10 h). There was significant decrease (P